2020
DOI: 10.1088/1742-6596/1507/3/032036
|View full text |Cite
|
Sign up to set email alerts
|

Structure of copper shaped charge liner evolution law based on die forging process

Abstract: Numerous studies have addressed the effect of grain size of materials on the overall penetrating performance of warheads. However, the use of the forging process to illustrate the grain heat-treatment refining technology has not been reported. In this experiment, the grain size of copper was observed and evaluated during the main processes of preparing copper shaped charge liners using the die forging process. Through this study, the evolution law for the structure of copper shaped charge liners was examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Comparison of the penetration results revealed that the shaped charge jet formed by liners with ultra-fine grain outperforms the coarse-grain liner in terms of penetration [ 11 , 12 ]. These studies imply that a smaller liner grain size is beneficial in improving jet performance and the methods of refining grain size during the die forging process have been studied [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the penetration results revealed that the shaped charge jet formed by liners with ultra-fine grain outperforms the coarse-grain liner in terms of penetration [ 11 , 12 ]. These studies imply that a smaller liner grain size is beneficial in improving jet performance and the methods of refining grain size during the die forging process have been studied [ 13 ].…”
Section: Introductionmentioning
confidence: 99%